Mergers and acquisitions of insurers in the context of globalization: the identification of trends - V. S. Musorenkov (Путеводитель предпринимателя, 2020)
The article is devoted to the issues of mergers and acquisitions of insurers in the conditions of globalization. Having reviewed the motivations and direction of transactions the author reveals their role in the development of the market, highlights contemporary issues of mergers and acquisitions of insurers, as well as possible the results of their implementation.